Comparison the effects of clinoptilolite supplementation on the nutritive value of rice bran and rice husk - W Mohd Madhi W Abdullah; Niza Syafiqah Hamzah; Noor Hidayah Dzkulfli; Nik Ahmad Nizam Nik Malek; Wan Zahari Mohamed (2014)
In this paper, the effects of clinoptilolite with and without supplementation on the nutritive value werecomparedbetweenrice bran (RB) and rice husk (RH). Five different levels of clinoptilolite (0-5%) were supplemented on RB and RH and the effects on the nutritive values were determined; dry matter (DM), total nitrogen (N), crude protein (CP), crude fat (EE), crude fibre (CF), total ash (Ash), calcium (Ca) and phosphorus (P) using the AOAC standard methods. Nitrogen free extract (NFE), total digestible nutrient (TDN) and metabolizable energy (ME) were calculated by differences. Increasing levels of clinoptilolite resulted in some changes in the nutritive values of RB and RH were not affected of EE and P content in RB, while affecting EE and P content in RH sample. Supplementation of clinoptilolite to RB and RH samples had increased DM, Ash, Ca and NFE contents, while decreasing total N, CP, EE, CF, P, TDN and ME in both samples but only P in RH is remain constant.